COVID-19: A Great Challenge for Public Health and the Economy in Colombia - Ferreira Cáceres, María Mercedes; Ramírez Cuadros, Cindy Gabriela; Matta Oyola, Piedad Gabriela; Barrera Cruz, Yislem Audrey (Revista Cuidarte, 2020)
The COVID-19 pandemic has generated a serious global crisis in which developing countries seem to be severely affected in Latin America and the Caribbean. This is a matter of concern given the poor working conditions and the high poverty rates in the region. The Colombian labor market has been severely affected by social distancing adopted to slow down the spread of COVID-19. However, human and economic losses caused by this pandemic, which does not discriminate, are countless. Facing this invisible enemy in a prudent and wise manner will be the greatest achievement in our history and finding a way to achieve it will be our most precious legacy for generations to come.How to cite this article: Ferreira Cáceres María Mercedes, Ramírez Cuadros Cindy Gabriela, Matta Oyola Piedad Gabriela, Barrera Cruz Yislem Audrey. COVID-19: Un gran desafío para la salud pública y la economía en Colombia. Revista Cuidarte. 2020; 11(3):e1318. http://dx.doi.org/10.15649/cuidarte.1318
Keywords: COVID-19; Pandemics; Economics; Public Health